Examining the Influence of Leadership Agility, Organizational Culture, and Motivation on Organizational Agility: A Comprehensive Analysis - Arifin, Rois; Purwanti, Henny (Manunggal Halim Jaya, 2023)
The primary objectives of this study encompass three main aspects: firstly, to determine and thoroughly analyze the influence of Leadership Agility on Organizational Agility; secondly, to ascertain and examine the impact of Organizational Culture on Organizational Agility; and finally, to establish and evaluate the effect of Motivation on Organizational Agility. To accomplish these objectives, a research methodology comprising descriptive analysis and multiple linear regression analysis was employed, with a sample size consisting of 85 respondents. The outcomes derived from the multiple linear regression analysis revealed several noteworthy findings. Firstly, it was observed that Leadership Agility exerted a positive and significant influence on Organizational Agility. This suggests that leaders who possess agile qualities, such as adaptability, flexibility, and effective decision-making, contribute significantly to enhancing the overall agility of the organization. Secondly, the study found that Organizational Culture also played a crucial role in shaping Organizational Agility. A positive and significant relationship was identified, indicating that a strong and supportive culture that values innovation, collaboration, and learning fosters organizational agility. Lastly, the analysis demonstrated that Motivation exhibited a positive and significant impact on Organizational Agility. Motivated employees who are driven by intrinsic and extrinsic factors, such as recognition, rewards, and a sense of purpose, contribute to a more agile organization. Overall, this research underscores the importance of Leadership Agility, Organizational Culture, and Motivation in driving and sustaining Organizational Agility. The findings emphasize the significance of cultivating agile leaders, fostering a supportive culture, and nurturing employee motivation to enhance an organization's ability to adapt, innovate, and thrive in a dynamic business environment.